Production of low-avidity antibody by infants after infection with serogroup B meningococci. - Pollard, A; Levin, M (2000)
Experimental serogroup B meningococcal vaccines have induced only poor immune responses and have had little protective efficacy in children younger than 1 year of age. We used ELISA with potassium thiocyanate to compare the average avidity of antibody produced by infants with that of children older than 10 years after systemic disease. Infants produced specific antibody of lower average avidity than older children--a finding that correlates with absence of serum bactericidal activity in the serum samples of the same infants.